When the Damage Is Done: Injury and Repair in Thymus Function - Kinsella, Sinéad; Dudakov, Jarrod A. (Frontiers in Immunology, 2020)
Even though the thymus is exquisitely sensitive to acute insults like infection, shock, or common cancer therapies such as cytoreductive chemo- or radiation therapy, it also has a remarkable capacity for repair. This phenomenon of endogenous thymic regeneration has been known for longer even than its primary function to generate T cells, however, the underlying mechanisms controlling the process have been largely unstudied. Although there is likely continual thymic involution and regeneration in response to stress and infection in otherwise healthy people, acute and profound thymic damage such as that caused by common cancer cytoreductive therapies or the conditioning regimes as part of hematopoietic cell transplantation (HCT), leads to prolonged T cell deficiency; precipitating high morbidity and mortality from opportunistic infections and may even facilitate cancer relapse. Furthermore, this capacity for regeneration declines with age as a function of thymic involution; which even at steady state leads to reduced capacity to respond to new pathogens, vaccines, and immunotherapy. Consequently, there is a real clinical need for strategies that can boost thymic function and enhance T cell immunity. One approach to the development of such therapies is to exploit the processes of endogenous thymic regeneration into novel pharmacologic strategies to boost T cell reconstitution in clinical settings of immune depletion such as HCT. In this review we will highlight recent work that has revealed the mechanisms by which the thymus is capable of repairing itself and how this knowledge is being used to develop novel therapies to boost immune function.